Principles of financial economics - LeRoy, Stephen F.; Werner, Jan (New york Cambridge university press, 2014)
The most important addition to the edition is the new Part Ten on the infinite-time security markets. It consists of three chapters that explore the consequences of assuming that time is infinite.
Includes bibliographical references and index.
osc 24/10/17
Loans
Keywords: Finance; Finance--Mathematical models; Investments--Mathematical models; Economics--Mathematical models; Securities--Prices--Mathematical models; Capital market--Mathematical models; Equilibrium (Economics)